2016
DOI: 10.1097/wnr.0000000000000480
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying movement intentions with multimodal neuroimaging for functional electrical stimulation-based rehabilitation

Abstract: Functional electrical stimulation (FES) is a common rehabilitation method for the purpose of recovery of paralyzed muscle by means of sequential electrical stimulation. Reports indicate that active participation by the patient, as opposed to simple stimulation, leads to improved recovery when using FES and other rehabilitation techniques. In this paper, we investigate the neurophysiological effect of an active participant's intention in the FES rehabilitation task. To observe the difference in brain signal bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The electrical and hemodynamic activation of the brain may be affected by the presence of intention. Moreover, only similar stimuli to voluntary movement like recognition of afferent information, imparting movement by the primary somatosensory cortex, could support cortical rearrangement during the flaccid phase of limb paralysis 27,28 . Therefore, treatment facilitating volitionally initiated exercises or appropriate sensory and proprioceptive feedback may improve shoulder subluxation 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrical and hemodynamic activation of the brain may be affected by the presence of intention. Moreover, only similar stimuli to voluntary movement like recognition of afferent information, imparting movement by the primary somatosensory cortex, could support cortical rearrangement during the flaccid phase of limb paralysis 27,28 . Therefore, treatment facilitating volitionally initiated exercises or appropriate sensory and proprioceptive feedback may improve shoulder subluxation 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Hara et al 32 revealed that EMG-triggered FES had more influence on blood cortical perfusion in the ipsilesional sensory-motor cortex than ES alone. Using near-infrared spectroscopy and electroencephalography, Lee et al 27 reported that the presence of intention affected the activation of the brain significantly in both hemodynamic responses and electrical patterns during ES.…”
Section: Discussionmentioning
confidence: 99%
“…Additional BCI research has investigated the utility of visual feedback which is a subtype of biofeedback (or neurofeedback) that uses real-time displays of brain activity so that subjects may perform self-regulation of their brain signals. It has been commonly employed in clinical therapies for Attention Deficit Hyperactivity Disorder (ADHD) [14], stroke [15], and user training in BCIs [16]. Previous studies have shown that visual or auditory feedback positively impacts typing speed, accuracy, and subjective experience [17].…”
Section: Introductionmentioning
confidence: 99%